2015
DOI: 10.1016/j.earlhumdev.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Selected vitamin D metabolic gene variants and risk for autism spectrum disorder in the CHARGE Study

Abstract: Background Vitamin D is essential for proper neurodevelopment and cognitive and behavioral function. We examined associations between autism spectrum disorder (ASD) and common, functional polymorphisms in vitamin D pathways. Methods Children aged 24–60 months enrolled from 2003 to 2009 in the population-based CHARGE case–control study were evaluated clinically and confirmed to have ASD (n = 474) or typical development (TD, n = 281). Maternal, paternal, and child DNA samples for 384 (81%) families of children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 34 publications
(47 reference statements)
0
36
0
1
Order By: Relevance
“…For example, paternal37 and individual38 39 vitamin D receptor (VDR) polymorphisms have been associated with increased ASD risk. We did not measure levels of vitamin D-binding protein, VDR or calcitriol (1,25D) which may have provided interesting insight here.…”
Section: Discussionmentioning
confidence: 99%
“…For example, paternal37 and individual38 39 vitamin D receptor (VDR) polymorphisms have been associated with increased ASD risk. We did not measure levels of vitamin D-binding protein, VDR or calcitriol (1,25D) which may have provided interesting insight here.…”
Section: Discussionmentioning
confidence: 99%
“…In an extensive epidemiological study, Childhood Autism Risks from Genetics and the Environment (CHARGE) showed an association between autism spectrum disorders (ASDs) and several functional polymorphisms in genes within the vitamin D pathway, including Bsm1, Taq1, Cdx2 and FokI in the vitamin D receptor (VDR) gene (Schmidt et al 2015). Importantly, this study pinpointed that the genotype AA/A-allele of GC rs4588, encoding the vitamin D-binding protein, was strongly associated with ASD in children (Schmidt et al 2015). Additionally, supplementation with high doses of vitamin D (ranging from 300 IU/kg/day to 5000 IU/day) in two open-label trials has been found to improve clinical core symptoms of autism in ~75% of affected children (Cannell 2017).…”
Section: Autism and Adhdmentioning
confidence: 99%
“…Multiple studies have reported inadequate VD status in children with ASD. Reduced intake and decreased exposure to UVB radiation have been considered as potential causes, but abnormal VD activity due to genetic polymorphisms of the genes encoding for the enzymes that hydroxylate VD 3 or in the gene that encodes VDR was found to be the most common reason (73)(74)(75). A 2016 meta-analysis of 11 studies, including 870 ASD children and 782 typically developing children, demonstrated signifi cantly lower serum 25(OH)D 3 concentrations in ASD cases than in controls (12).…”
Section: Vitamin D Deficiency In Childrenmentioning
confidence: 99%